The Relationship Between Family Support And Compliance With Routine Control Of Pulmonary TB Patients At UPTD Puskesmas Teluk Dalam Nias Selatan - Nainggolan, Syahrul Handoko; Hulu, Yurdina (SEAN Institute, 2023)
Pulmonary TB or tuberculosis is an infectious disease caused by rod-shaped bacteria, namely Mycobacterium tuberculosis. Usually the most commonly infected are the lungs but can affect other organs. The disease can be transmitted from person to person through droplets from people infected with pulmonary TB. Treatment of tuberculosis depends on the patient's knowledge, socioeconomic circumstances as well as support from family. The lack of effort from oneself or lack of support from family for complete treatment will affect patient compliance to undergo brand treatmentThe purpose of the study was to determine the relationship between family support and compliance with routine control in TB patients. Lung at UPTD Teluk Dalam Health Center in South Nias in 2022 This study is a quantitative research using a correlation descriptive design with a cross-sectional observation approach. The results of the study showed a positive and significant relationship between Family Support and Adherence to Routine Control in TB Patients. Lung at UPTD Puskesmas Teluk Dalam Nias Selatan result p = 0.017. The conclusion of the study is that there is a relationship between family support and adherence to routine control in TB patients. Lung at UPTD Puskesmas Teluk Dalam Nias Selatan.